Analysis af Informal Economic Education Based on Local Potential in Seaweed Farming Communities in Pabiringa Village, Jeneponto Regency - INANNA, INANNA; Pirayanti, Pirayanti; Nurdiana, Nurdiana; Hasan, Muhammad; Tenri Ampa, Andi (International Journal of Applied Economics, Accounting and Management (IJAEAM), 2023)
This study aims to determine the analysis of informal economic education based on local potential in seaweed farming communities in Pabiringa Village, Jeneponto Regency. This research is a qualitative descriptive research. This research uses data collection techniques carried out by observation methods, interview methods, and documentation. The subjects in this study are seaweed farming communities, namely parents and children. Data analysis techniques in this study use data reduction, data presentation, and conclusion drawing. The results of this study show that the stages of informal economic education are very important to increase children's potential in fostering economic awareness in children from an early age through habituation, example and knowledge transfer. Just as parents train and accustom children to save, parents teach children to manage pocket money in distinguishing wants and needs and developing an entrepreneurial spirit. However, not all seaweed farming communities can provide economic education to their children because of their own difficulties in educating children, busy work and lack of insight and knowledge of parents about the importance of economic education for their children. thus making children not independent and continue to depend on parents to meet their needs. Seaweed farming communities need to overcome and also balance between busy work and educating their children at home such as teaching saving, money management, and also developing entrepreneurial spirit.